Nucleotide Structure and Characterization of the Murine Gene Encoding Anticoagulant Protein C - Jalbert, Louise R.; Rosen, Elliot D.; Lissens, Ann; Carmeliet, Peter; Collen, Désiré; Castellino, Francis J. (Thrombosis and Haemostasis, 1998)
The 15,160 bp murine gene encoding anticoagulation protein C (PC) was cloned and sequenced, including 414 bp upstream of exon 1 and 80 bp downstream of the translation stop codon. Nine exons and eight introns were identified. The first exon was untranslated and contained the major transcriptional start site, the surrounding nucleotide sequence of which matched reasonably well with the consensus eukaryotic Cap element sequence. The translational initiator methio-nine residue was located in exon 2. The other introns were positioned as splices between the major domain units of the protein. The 5’ untranslated region contained two possible CCAAT sequences and GC boxes, but no TATA box was obvious within the optimal range of distances from the transcription start site. The 3’-flanking nucleotides included a probable polyadenylation site (ATTAAA), beginning 80 nucleotides downstream of the translation stop codon, and a downstream consensus sequence (AGTGTTTC) required for the efficient formation of a 3’ terminus of mRNA. Several high probability transcription factor recognition sequences, including proteins that are enriched in, or specific to, the liver, such as C/EBP, C/EBP, HNF1, and HNF3, have been located in the 5’ region of the gene. These results indicate that all elements are present for liver-based transcription of the gene for murine PC.